If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x-4=3x+1+9x-5
We simplify the equation to the form, which is simple to understand
7x-4=3x+1+9x-5
We move all terms containing x to the left and all other terms to the right.
+7x-3x-9x=+1-5+4
We simplify left and right side of the equation.
-5x=0
We divide both sides of the equation by -5 to get x.
x=-0
| -4-7x=2x+15 | | 4r-9=55 | | 4x+14(-14)-3+(-14)= | | 16+8x=24+6x | | -4(-x+4)=-4x+16 | | 16-4x= | | 7x-4=-3x+1+9x-5 | | x(30-x)=176 | | -94=-17+-7m | | -4(x-4)=-4x+16 | | 7n=50+35 | | 5x-10=14+7x | | 0.2x+0.15(50)=25.5 | | 5=RAIZ(2)+6RAIZ(3)+RAIZ(2)-2RAIZ(3) | | (-9r^3+2r-1)-(-5r^2+6x^2)= | | y=x(x^2-3) | | 8w-21=11 | | -3(-4-6y)+7(-y-5y)=-8 | | 4(1x+9)=56 | | 10(12-5)= | | -m+68=10 | | -3(-4-6y)+7(-y-5w)=-8 | | 10+8q=11+7q | | 85=10-2.5(c) | | 28=5x-2x+4 | | (5x^2-3x+7x)+(4x^2+2x^2+7x)= | | 3y-4y=-4y+29 | | 6(x-1)+3=13 | | 22+4y=50 | | 5x^(2/3)-19x^(1/3)-4 | | 4(d-8)+11= | | 8a-8=-3a+88 |